Faktor yang Mempengaruhi Kondisi Psikologis dan Stigma pada Masa Pandemi Covid-19 - Susanto, Joko; Makhfudli, Makhfudli; Ubudiyah, Masunatul; Rukanah, Rukanah; Sairozi, Ali; Ilkafah, Ilkafah (FORIKES, 2022)
Corona virus Disease 2019 causes health problems in the world in the form of a health crisis which results in psychological problems such as fear and anxiety. So a study is needed to find out the factors that influence psychology and stigma during the Covid-19 pandemic. Study was a literature review based on 5 databases (Scopus, CINAHL, Science Direct, PubMed, and ProQuest), involving cross-sectional or quasi-experimental, in March 2021. Center for Review and Dissemination and JBI Guidelines were used to measure quality and checklists PRISMA for guide reviews. Feasibility study based on title, abstract, full text, and research method. Eleven articles met the criteria. Most of the factors related to psychological conditions and stigma have a quasi-experimental and cross-sectional design. The mean number of participants was over 1,000 for each study and discussed psychological conditions and factors associated with social stigma. Factors related to psychological conditions were age, education, gender, symptoms and health conditions, information, economy, exposure duration and social support, while factors related to stigma were environment, history of comorbid illnesses, discrimination, and community perceptions.Keywords: psychological condition; stigma; Covid-19 ABSTRAK Corona virus Disease 2019 menimbulkan masalah kesehatan di dunia berupa krisis kesehatan yang mengakibatkan masalah psikologis seperti rasa takut and cemas. Maka diperlukan studi untuk mengetahui faktor yang mempengaruhi psikologis dan stigma selama pandemi Covid-19. Studi merupakan literature review berbasis 5 database (Scopus, CINAHL, Science Direct, PubMed, dan ProQuest), yang melibatkan cross-sectional atau kuasi-eksperimental, pada bulan Maret 2021. Pusat Tinjauan dan Diseminasi dan Panduan JBI digunakan untuk mengukur kualitas dan daftar periksa PRISMA untuk ulasan panduan. Studi kelayakan berdasarkan judul, abstrak, teks lengkap, dan metode penelitian. Sebelas artikel memenuhi kriteria. Sebagian besar faktor yang berhubungan dengan kondisi psikologis dan stigma memiliki desain kuasi eksperimental dan cross-sectional. Rerata peserta adalah lebih dari seribu untuk setiap studi dan membahas kondisi psikologis dan faktor yang terkait dengan stigma sosial. Faktor yang berhubungan dengan kondisi psikologis adalah usia, pendidikan, jenis kelamin, symptoms and health conditions, informasi, ekonomi, exposure duration dan social support, sedangkan faktor yang berhubungan dengan stigma adalah lingkungan, riwayat penyakit komorbid, diskriminasi, dan persepsi masyarakat.Kata kunci: kondisi psikologis; stigma; Covid-19